Pengaruh Spiritual Leadership dan Employee Resilience terhadap Employee Performance Dimediasi Work Engagement di Bank BUMN Jakarta Timur - An Nisa Septianna Janitra; Netania Emilisa; Gibran Julian Aldebaran (Syntax Corporation Indonesia, 2024)
This study aims to analyze Spiritual Leadership, Employee Resilience, Work Engagement, and Employee Performance, as well as the relationship between them, including the influence of Work Engagement mediation. Hypothesis testing was used to test the influence of Spiritual Leadership and Employee Resilience research on Employee Performance mediated by Work Engagement on employees of State-Owned Banks in East Jakarta City. Since the relationship between variables is explained, a type of correlational research is used. Because the data used is only used once per period, it is cross-sectional and the unit of analysis is an individual, namely an employee of a state-owned bank in East Jakarta City. The results of hypothesis testing show that there are great benefits between Spiritual Leadership and Employee Resilience on Employee Performance, as well as between Spiritual Leadership and Employee Resilience on Work Engagement. However, there was no significant positive effect between Work Engagement on Employee Performance, nor the effect of Work Engagement mediation on the relationship between Spiritual Leadership and Employee Resilience on Employee Performance.